Evaluating the US Decision to Get Involved in the 2003 Iraq War Using a Bureaucratic Politics Model - Arfiansyah Putra Pradana Hadi; Ahmad Farhan Dzaky Kafrawi; Rahman Chalimi, Mohammad Mazi Fatur (Journal of Integrative International Relations, 2024)
This comprehensive policy brief delves into the intricate US decision to engage in the 2003 Iraq War, shedding light on the multifaceted aspects that influenced this pivotal moment in international relations. The Iraq War is renowned for its controversy and profound global repercussions, making it an essential subject of study. The evaluation framework utilized in this research is the Bureaucratic Politics Model, which scrutinizes the inner workings of the US government in foreign policy decisions. To understand the depth of this decision, the research encompasses an extensive analysis of the political, economic, military, and diplomatic landscape that surrounded the choice to invade Iraq. This investigation uncovers the inner dynamics of US foreign policy by highlighting the roles and diverse objectives of key decision-makers within the government, offering valuable insights into the complexity of the decision-making process. The findings underscore the significance of internal factors in shaping foreign policy and emphasize the need for transparency within the decision-making process. Furthermore, it underscores the importance of prioritizing diplomacy as a tool for conflict resolution and the necessity of considering the long-term consequences of foreign policy decisions. In a world where international relations are ever-evolving, this research serves as a poignant reminder of the intricacies of foreign policy and its far-reaching implications.